Androgen receptor, aromatase, oestrogen receptor α/β and G protein‐coupled receptor 30 expression in the testes and epididymides of adult sheep. Issue 4 (17th February 2020) - Ge, Wenbo; Xiao, Longfei; Duan, Hongwei; Jiang, Yuting; Lv, Jianshu; Ding, Ziqiang; Hu, Junjie; Zhao, Xingxu; Zhang, Yong
Abstract: The androgen receptor (AR) plays a key role in reproduction, and aromatase (P450arom), nuclear oestrogen receptors (ERs) α and β, and G protein‐coupled receptor 30 (GPR30) are important for testicular and epididymal cell proliferation and development. In the study, we have investigated the expression and localization of AR, P450arom, ERα, ERβ and GPR30 in testes and epididymides of sexually mature sheep by quantitative reverse transcription–polymerase chain reaction, Western blotting and immunohistochemistry. The results demonstrate that the AR, P450arom and ERα levels in the caput and corpus epididymis were significantly lower than those in the testis and cauda epididymis ( p  < .05), the ERβ level in the testis was significantly higher than in the caput, corpus and cauda epididymis ( p  < .05), and the GPR30 level in the caput epididymis was significantly lower than in the testis and corpus and cauda epididymis ( p  < .05). These receptors were mainly detected in epididymal epithelial, basal, smooth muscle, Sertoli and Leydig cells, as well as in spermatozoa. Taken together, the results suggest that sheep epididymides and testes have the potential for estradiol synthesis and are the targets of both androgens and estradiol. These results provide a foundation for further studies on the mechanisms of androgens and estradiol signalling in the testes and epididymides of sheep.